A harvesting help contract - Puślecki, Damian (Przegląd Prawa Rolnego, 2018)
The purpose of this article is to define the normative form of a harvesting help contract and to resolve any doubts that may arise in its practical application. Due to the occurrence of accidents in agriculture, it is also necessary to answer the question to what extent the legal regulation of agricultural social insurance should provide protection for farmers’ helpers (assistants) against the loss of their ability to work. In conclusion, the author states that the Insurance Act regulates a new type of contract − a harvesting help contract − but the scope of its regulation raises serious doubts. The legislator has introduced a non-synthetic definition of the term and while only vaguely defining the rights and obligations of the farmer, defines in too much detail those of the helper. The analysed regulation does not provide for any specific form of the contract or its contents regarding the activities of duties performed during harvesting or the level of pay for the work provided. The protection of the helper is limited to the provision of health insurance and accident insurance benefits only. In view of the subject of insurance protection and the specificity of work in agriculture, such a narrow structure, does not seem to be justified.